2012
DOI: 10.1038/ajh.2011.244
|View full text |Cite
|
Sign up to set email alerts
|

Association of left ventricular mass with the AGTR1 A1166C polymorphism

Abstract: LV mass index is associated with the AGTR1 A1166C polymorphism. Further research should clarify to what extent this association might be mediated via different expression of AGTR1 as modulated by microRNA-155.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
16
0
7
Order By: Relevance
“…In the present study, we have found increased septal and anterior wall thickness in uremic animals. Additionally, plasma ANG II level, which is an indirect marker of hypertension and left ventricular hypertrophy (20,27,28,43,58), was also higher in uremic rats. These results together with literature data (1,33,38,41) suggest the development of a minimal left ventricular hypertrophy in uremic animals at week 30 in our present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, we have found increased septal and anterior wall thickness in uremic animals. Additionally, plasma ANG II level, which is an indirect marker of hypertension and left ventricular hypertrophy (20,27,28,43,58), was also higher in uremic rats. These results together with literature data (1,33,38,41) suggest the development of a minimal left ventricular hypertrophy in uremic animals at week 30 in our present study.…”
Section: Discussionmentioning
confidence: 97%
“…Immediately after excision of the heart, blood was collected from the thoracic cavity to measure plasma uric acid, carbamide, and creatinine levels to verify the development of uremia. Some plasma was used for the determination of ANG II as an indirect marker of hypertension and hypertrophy (20,27,28,43,58) and nitrotyrosine as a marker of systemic nitrosative stress (7). To assess the cardioprotective effect of ischemic preconditioning in the hearts of uremic and sham-operated animals, the perfused hearts were subjected to ischemia/reperfusion with or without preconditioning protocol.…”
Section: This Investigation Conforms To the National Institutes Of Hementioning
confidence: 99%
“…Вместе с тем, результаты многоцентровых исследований по ассо-циации SNP А1166С гена AGT2R1 с риском развития БСК для разных этнических групп противоречивы и неоднозначны. Единичные работы в России не отражают генетического разнообразия в распреде-лении 1166С полиморфизмов гена AGT2R1 и их ассо-циаций с ССЗ [8][9][10][11][12][13][14][15].…”
Section: Discussionunclassified
“…С1166С генотип и 1166С аллель ассоциированы с повышенным риском развития сердечно-сосудис-тых заболеваний и, в частности, коронарного атеро-склероза [9,10,12,14,15].…”
Section: литератураunclassified
“…A recent study showed a miR signature in plasma of patients with essential hypertension, which differed from their healthy counterparts: 27 miRs were differentially expressed. 9 The evidence for the interplay among miR-155, the angiotensin receptor 1, A1166C polymorphism, and angiotensin receptor 1 protein expression levels 10,11 provides a possible pathogenetic role for a miR in cardiac hypertrophy, whereas the description of a genetic variant in the 3′ untranslated region of vacuolar H+ ATPase ATPV0A1 creates a miR-637-binding motif related to hypertension risk by interfering with the fine-tuning of several vasoactive substances, including chromogranin A as precursor of catestatin, an inhibitor of catecholamine release. 12 A refreshing point of view would be to study the effect of antihypertensive medication on miR profiles.…”
Section: Are Mirs Of Pathogenetic Importance In Arterial Hypertensionmentioning
confidence: 99%